Time Course of Changes in Humoral Immunological Factors During Perioperative Nutritive Maintenance - O. V. Dorofeyev; I. Z. Kitiashvili (Общая реаниматология, 2007)
Objective: to study perioperative humoral immunity (IgA, IgM, IgG, and CD19+) during nutritive maintenance in patients with acute destructive calculous cholecystitis.Subjects and methods. The study was based on the results of studying probe nutritive maintenance in patients with acute destructive calculous cholecystitis intraoperatively and on days 1—3 after cholecystectomy. In the study group, nutritive maintenance using a polymer balanced lactose-free dry Berlamine-Modular formula (Berlin-Chemie, Germany) was made in 34 patients. A control group comprised 29 patients. An option of intermittent administration of the feeding formula was chosen for nutritive maintenance.Results. Perioperative nutritive maintenance in patients with acute destructive calculous cholecystitis improved humoral immunological parameters and reduced the incidence of postoperative and pyoinflammatory complications and the length of hospital stay.